Factors influencing mathematical problem solving performance among Malaysian matriculation students - Abu Bakar, Suriati (2019)
This research was conducted to identify the relationship between mathematics beliefs, mathematics attitude, mathematics self-efficacy, metacognitive skills and mathematical problem solving performance among Malaysian matriculation students. For this purpose, a total of 312 matriculation students from three matriculation colleges were selected as respondents. The data were analysed by using IBM SPSS. All the independent variables were measured using a questionnaire while mathematical problem solving performance was measured using a mathematical test. A descriptive analysis was carried out to obtain both the mean and standard deviation of the variables. The findings showed that students had more positive beliefs and positive attitude in mathematical problem solving. Besides, students also had shown increase in mathematics self-efficacy and metacognitive skills in mathematical problem solving. Based on the analysis of the mathematical problem solving test, it was revealed that majority of the students performance in solving non-routine problems is still at unsatisfactory level. The outcomes of this research showed that their ability to understand problem, to plan a solution and execute correct answer are low.